Profit - the role of world class strategic marketing planning - McDonald, Malcolm (Henry Stewart Talks, 2012)
The need for marketing planning, Key elements of world class marketing, How to begin the process, How to understand your market, How to segment your market, How to understand your customers' needs, How to prioritise your marketing objectives and strategies, how to test the value of your marketing plan